PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA LAMPUNG - Satimin, Satimin; Nawawi, Muhammad (Jurnal Trisna Riset, 2025)
Quality human resources and a high work ethic are the main assets for an organization to be able to compete with other organizations. Without the initiative of each individual to try to advance voluntarily, the organization will not have any meaning. Motivation is an important factor that can influence employee productivity and performance in an organization. Employees who have high motivation tend to show better performance, which has an impact on achieving company goals. At PT. Indomarco Prismatama Lampung, it turns out that motivation has not been implemented properly so that employee performance is not optimal. The problem faced is how motivation influences employee performance at PT. Indomarco Prismatama Lampung. The purpose of this research is to determine the effect of motivation on employee performance at PT. Indomarco Prismatama Lampung and is useful as reference material for further research regarding employee motivation and performance. The hypothesis proposed is that motivation has a positive effect on employee performance at PT. Indomarco Prismatama Lampung. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, a correlation was obtained between motivation in efforts to improve employee performance at PT. Indomarco Prismatama Lampung obtained an r number of 0.68. After consulting with conservative standards, it is between 0.600-0.799 which is considered a strong correlation. So it can be said that there is a strong influence between motivation on employee performance at PT. Indomarco Prismatama Lampung. This research is expected to provide insight for management in designing strategies to increase employee motivation to improve overall performance.